The Effect of Profitability and Leverage on Corporate Social Responsibility Disclosure: Case Study on Sharia Commercial Banks in Indonesia - Andriani Andriani; Defi Masliha (Cahaya Abadi Publisher, 2023)
A profitability ratio is a ratio to assess the company's ability to seek profits. The leverage ratio is a measure of the number of assets that are financed with debt. These two ratios can influence the company in expressing its social responsibility. The purpose of this study was to determine the effect partially and simultaneously between the profitability variable is proxied using Return on Asset (ROA) and the leverage is proxied using the Debt Equity Ratio (DER) on corporate social responsibility disclosure (CSR). The population in this study were 14 Islamic Commercial Banks (BUS) in Indonesia from 2015 - 2019. This study using five periods so that the sample data obtained was 70. The sampling technique in this study was carried out using saturated sampling. And the data collection technique in this study is to use documentation analysis in the form of BUS reports that reveal annual reports, sustainability reports, and reports on CSR during the 2015 - 2019 period. Sourced from the web addresses of each bank. The analysis results obtained show that: 1) Profitability does not affect CSR disclosure 2) Leverage has a significant effect on CSR disclosure 3) The effect of profitability and leverage on CSR disclosure is 27.9% and the remaining 72.1% is influenced by other variables not examined.